1998
DOI: 10.1079/bjn19980073
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid levels in maternal milk: differences with respect to ascorbic acid status during the third trimester of pregnancy

Abstract: The aim of the present investigation was to study the relationship between ascorbic acid status during the third trimester of pregnancy and levels of this vitamin in transition milk (days 13-14 of lactation) and mature milk (day 40 of lactation). To this end, the pregnancies and lactation periods of fifty-seven healthy women between 18 and 35 years of age (27 (SD 3.7) years) were monitored. Vitamin intake during the third trimester was determined by recording the consumption of foods over 5d, and by registerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…In one group, 21.2% of women were found in this category 17 . These women ate less fruit (148X8^78X9 g day 21 compared with 398X1^221X9 g day 21 for women who ate adequate amounts) and vegetables (145X5^44X9 g day 21 compared with 275X11 04X9 g day 21 among those whose vitamin C intake was adequate).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In one group, 21.2% of women were found in this category 17 . These women ate less fruit (148X8^78X9 g day 21 compared with 398X1^221X9 g day 21 for women who ate adequate amounts) and vegetables (145X5^44X9 g day 21 compared with 275X11 04X9 g day 21 among those whose vitamin C intake was adequate).…”
mentioning
confidence: 99%
“…Their serum vitamin C levels were less satisfactory. Later, their transition milk content of vitamin C was lower (255X5^220X3 mmol l 21 compared with 437X8^288X4 mmol l 21 for those with better vitamin C intakes) 17 . At birth, the child passes from a low-oxygen to a highoxygen environment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At stable intakes, vitamin C concentrations in fasting plasma correlate directly and significantly with platelet, erythrocyte and leucocyte concentrations (Jacob et al 1987;Levine et al 1995;Graumlich et al 1997), and fasting plasma concentrations of > 60 µmol ascorbic acid/l indicate tissue saturation (Graumlich et al 1997). However, there is no established plasma threshold defining deficiency, and plasma ascorbic acid concentrations of > 11·4, > 17, and > 22·7 µmol/l have been regarded as acceptable (see Ortega et al 1998). In depletion studies of healthy young men plasma vitamin C concentrations decreased to an average of 7 µmol/l without clinical signs of scurvy (Jacob et al 1987;Graumlich et al 1997).…”
Section: Vitamin C Status: Relationship Between Intake and Body Storesmentioning
confidence: 99%
“…This increased physiological demand for vitamin C is accompanied by intensified food cravings, primarily for sweet foods [33]. Though the advent of artificially sweetened foods may have diminished the utility of such cravings, a meta-analysis of studies of gestational cravings found that fruit and fruit juice are nevertheless the most frequently reported target of gestational cravings [37]; and moreover a correlation between fruit consumption during pregnancy and serum vitamin C levels has been demonstrated [86]. Though the molecular basis for gestational cravings is not wellunderstood, endogenous opioids are implicated both by the specificity of cravings and by the many disturbances in the endogenous opioid system known to occur during gestation.…”
mentioning
confidence: 99%